HUBUNGAN PERATURAN DAERAH KOTA MAKASSAR TENTANG ZAKAT DENGAN HUKUM ISLAM - Mulasari, Mita; Hasan, Hamzah; Risal, M. Chaerul (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
This study aims to find out how the relationship between Makassar City Regional Regulation Number 5 of 2006 concerning Zakat Management and Islamic law. This type of research is field qualitative with a sociological juridical approach and normative theology of syar'i. The decentralization system provides space for local governments to form regulations as one of the legal instruments, and the Makassar City Government has taken advantage of this authority by establishing Regional Regulation Number 5 of 2006 concerning Zakat Management as an effort to maximize the potential of zakat in reducing poverty, especially since the population of Makassar City is predominantly Muslim. Materially, the local regulations do not conflict with the obligations of charity ordered by the Qur'an, even their existence serves as a reinforcement of the obligations of charity for Muslims, and the formalization of religiosity values into positive law is not new, because previously various law-level regulations have been born such as the Marriage Law, the Zakat Management Law, and the Hajj Implementation Law, so that its existence can be ensured that it does not conflict with Islamic law and even has a very close relationship.